WO3-Based Materials as Electrocatalysts for Hydrogen Evolution Reaction - Li, Yixuan; Zhai, Xiaoliang; Liu, Yong; Wei, Huijie; Ma, Junqing; Chen, Min; Liu, Xianming; Zhang, Wanhong; Wang, Guangxin; Ren, Fengzhang; Wei, Shizhong (Frontiers in Materials, 2020)
Environmental pollution and energy shortage make the development of clean energy more and more urgent. As a kind of clean renewable energy, hydrogen has attracted more attention recently. WO3-based materials have emerged as one of the most promising candidates for electrocatalytic hydrogen evolution reaction (HER), due to their attractive electrocatalytic activity, low cost as well as the electrochemical durability. In this minireview, we systematically provide an overview of WO3-based materials applied for HER, including pure WO3, the doped WO3 and the WO3-based composite materials. Furthermore, the strategies to enhance their electrocatalytic performance are summarized and discussed, such as morphological engineering, doping, as well as compositing with other materials. Finally, the limitation and challenges of WO3-based materials for HER and their prospects for future research are proposed. We believe that this minireview will be favourable for scientists to seek more promising HER electrocatalysts.